Peer Educator Permainan Tradisional (PD-Games) sebagai Alternatif Solusi Peningkatan Aktivitas Fisik dan Fleksibilitas bagi Anak Sekolah - Atikah Rahayu; Eka Swasta Budayati; Enggista Hendriko Delano (Jurnal Medika: Medika, 2026)
Increasing trend in the proportion of school children to teenagers with physical activity categories below WHO recommendations. This has implications for increasing obesity and as a gateway to degenerative diseases when children grow up. The aim of the service is to improve the behavior and flexibility of school children. The PkM design is 3 stages, namely the preparation stage, the service team collaborates to develop PD-Games for students. The program implementation phase will be held on Tuesday, August 19 2025 at 07.30-09.30 WIB indoors and on the field at the Muhammadiyah Mertosanan Elementary School, Bantul. The number of participants present was 30 people (students), 2 PJOK/UKS accompanying teachers as well as the school principal and curriculum team to make PkM a success. The evaluation stage is carried out by the service team to evaluate a series of service activities. The evaluation results show that participants participated in all series of traditional games. The measurement results for both the female and male groups showed an increase in flexibility for both with the Mean±SD for males being greater than for females, namely 28.94±2.14 (males) and 27.43±2.71 (females), the results of interviews with both PJOK/UKS teachers, school principals and the curriculum team recommended that similar activities, and modifications with competitions need to be carried out again so that the application of traditional games continues to develop.